Identification of novel targets for cancer chemotherapeutic agents : design, synthesis and evaluation of chromene based compounds with affinity for steroid hormone receptors - Egan, Billy (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2013)
Breast cancer is the second most common cancer in Ireland and accounts for 28% of all cancers in women in Ireland, with an average of 1726 new diagnosis each year. One of the major therapeutic advances in clinical treatment of breast cancer has been the introduction of selective estrogen receptor modulators (SERMs). Tamoxifen is a selective estrogen receptor modulator (SERM) with a triarylethylene structure which acts as an estrogen antagonist in the breast. This drug is used extensively and successfully as an endocrine treatment for breast cancer. However, it can also act as an agonist in endometrial tissue resulting in unwanted side effects including endometrial cancer. A variety of modified triarylethylene SERM structures have been developed based on the non-isomerisable scaffold structures such as raloxifene. The vast majority of early stage breast cancers, in both pre- and postmenopausal women, are hormone-dependent. The human hormone estradiol has an important role in the progression of breast cancer. The key feature of the SERMs, which are chemically diverse compounds, is that they contain a tertiary structure that enables them to bind to the estrogen receptor. The successful discovery of new drugs for cancer chemotherapy requires a combination of chemical and biochemical data and is both a costly and challenging task. Using in silico high throughput screening (HTS) methods, a novel series of estrogen receptor antagonists featuring the chromene scaffold has been discovered. In this thesis a comprehensive library of structurally related chromene compounds has been synthesised and evaluated. These compounds provide a resource of small-molecule BAR (structure-activity relationship) data, which can be used to guide lead compound identification in the area of drug discovery for estrogen receptor antagonists. These novel structures are designed to incorporate the potent chromene scaffold structure, and the data provides promising evidence for use of the benzopyran and pyranocoumarin ring scaffolds as an effective method for producing large libraries of novel compounds with interesting biochemical activities. Thirteen different libraries of benzopyran and pyranocoumarin compounds were synthesised (Chapter 2) and evaluated for antiproliferative activity in vitro in MCF-7 estrogen receptor positive human breast cancer cells (Chapter 3). These compounds bind to the estrogen receptor, while also inhibiting the proliferation of a human MCF-7 breast carcinoma cell
Keywords: Pharmaceutical Chemistry, Ph.D.; Ph.D. Trinity College Dublin